1989
DOI: 10.1046/j.1537-2995.1989.29589284136.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of pooled platelet concentrates

Abstract: The use of sterile connecting devices will permit up to 5-day storage of pooled platelet concentrates (PCs). However, there are no data evaluating long-term storage of PCs pooled from multiple donors. Four units of ABO-compatible or -incompatible PCs were pooled and stored in single 300-ml PL-732 storage bags for up to 5 days. Results of in vitro assays showed acceptable storage values regardless of the ABO types in the pool. Pool pH on Day 5 was 6.83 +/- 0.3 (mean +/- 1 SD). The in vitro storage characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 12 publications
9
34
0
Order By: Relevance
“…These results are in concordance with observations of Snyder et al [18] and Moroff et al [19]. They studied lymphoprolifér ation by measurement of 3H-thymidine uptake in pools of PC from platelet-rich plasma.…”
Section: Evaluation Of Lymphoprolifération In Stored Bc-pcsupporting
confidence: 91%
“…These results are in concordance with observations of Snyder et al [18] and Moroff et al [19]. They studied lymphoprolifér ation by measurement of 3H-thymidine uptake in pools of PC from platelet-rich plasma.…”
Section: Evaluation Of Lymphoprolifération In Stored Bc-pcsupporting
confidence: 91%
“…This reduction in platelet counts parallels the 5.5% drop in counts observed in 17/20 LR PCs over the same period. The tendency for platelet counts of PCs recovered from whole blood to apparently increase from day 0 to day 5 has been previously documented by a number of other investigators [45, 46, 47]. …”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, it was observed that leukocyte-derived cytokines are not detectable in PC with a leukocyte contamination below 0.1 × 10 9 [10, 16]. Several groups investigated the risk that passenger PBMC from different individuals in pooled PC generate mixed lymphocyte reactions during storage [17, 18]. However, no evidence for the generation of activated lymphocytes or lymphoproliferation such as 3 H thymidine uptake could be found, but the reason for this remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The strong impact of temperature and anticoagulant on cytokine release could explain why several groups failed to detect signs of lymphoproliferation in pooled PC [17, 18]. On the other hand, cytokine production was not totally abrogated at 22 °C with CPD.…”
Section: Discussionmentioning
confidence: 99%